Effect of noninvasive castration method on weight gain, behavior and meat quality of ram lambs - Czoller, Rebeka; Rózsa-Várszegi, Zsófia; Balogh, Péter (Acta Agraria Debreceniensis, 2022)
In the course of producing heavyweight lambs (above 35 kg), males need to be separated from females at the end of the fattening period.  If not, the rams must be castrated because they reach sexual maturity, and their activity bothers the ewes or unwanted pregnancy may occur. The present study surveys if the Hungarian sheep keepers know or use the non-surgical elastrator method for castration and assess the effect of castration (surgical and non-surgical) on daily weight gain, behavior, moving activity, and meat quality of rams, respectively. We found many advantages regarding the use of the elastrator method. Based on the survey results, 100% of farmers who used elastrator had a positive experience and favorable opinion about this method. There is no need to separate the rams, which allows for less area requirement and more economical technological conditions. The traditional castration (with a knife) process is longer (4–6 minutes), and caused longer-lasting stress while the elastrator application is bloodless, took only 20–30 seconds, and were stress-free. The number of steps of ring-gelded individuals was much lower than that of the non-castrated rams. The difference in steps number could also be seen in ewes separated into different ram groups. The weight gains of individuals castrated by the ring were better than the surgically castrated ones and also individuals with testicles. The palatability of the meat from the non-castrated group was less favorable, and the chewiness of the ringed group was the best. Finally, our results highlighted the benefits of the noninvasive elastrator method in animal welfare aspects.